An understudied population? Exploring the factors associated with fear of crime in a semi-rural environment. Issue 2 (1st February 2022) - Lytle, Daniel; Intravia, Jonathan; Randa, Ryan
ABSTRACT: The intersection of fear of crime and media consumption has been examined in urban environments extensively. However, like many aspects of criminal justice research, much less is known about these concepts in non-urban environments. Further, there is an assumption that the processes of how media will influence fear of crime will work similarly in non-urban environments. This question remains open to empirical examination. In this paper, we investigate the relationship between media consumption and fear of crime in a semi-rural environment. Using data collected via telephone survey, and conducted within a selected non-urban community, we examine the relationship between media consumption and fear of crime while controlling for a host of confounders. Results indicated that media consumption is related to fear of crime among this specialized sample. However, this relationship becomes nonsignificant once perceived disorder is introduced. Findings and implications are discussed.